Discourse and Semiotic Analysis of The Political Campaign Videos Broadcasted on Social Media in The 2020 Presidential Elections Held in The Turkish Republic of Northern Cyprus - Oshan Uluşan; İzlem Kanlı (Connectist Istanbul University Journal of Communication Sciences)
Politics and communication work in tandem to determine the practices pertaining to political communication. The objective of reaching out to large masses in general as well as citizens from target constituencies is a determining factor for political candidates in the success of political campaigns. Therefore, besides leveraging traditional mass media, incorporating social media strategies to drive political communication processes expands the area of influence of political communication activities, thus directly influencing the political turnouts and increasing the effectiveness of the campaign. As a result of the maximum political commercials featured on social media during this election, the 2020 Presidential Elections held in the Turkish Republic of Northern Cyprus (TRNC) is an important benchmark in the history of political communication in the TRNC. Therefore, in this study, candidates’ political advertising videos are analyzed through semiotic and discourse analyses. These These analyses revealed that issues such as uncertainties regarding the future, freedom, democracy and independence related to the Cyprus Dispute, were reproduced around the ideologies of candidates and that these were presented through political advertising videos with cultural, social and political codes. Thus, the findings obtained in this study will contribute to the analysis of TRNC political communication and discourse.